Selektivitas Gillnet Dasar Terhadap Hasil Tangkapan Ikan Baronang di Perairan Teluk Ambon Dalam - Deni Sarianto; Kadi Sarianto; Untung Prasetyono; Kemhay Kemhay; Muhidin Syamsuddin; Wulandari Wulandari (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
This research was aimed at analyzing the selectiveness of bottom gillnet mesh size on the rabbitfish catch in the inner part of Ambon Bay. The research method used descriptive case study and data analysis used T-test. The results of this research indicate a 3.5 inch of the bottom gillnet mesh size is more selective than 2.5 inch. The larger mesh size, the bigger fish will be captured. Based on t-test in regression model that total length of the rabbitfish has a significant effect on the ratio of the number of fish catches bottom gillnet of the two mesh sizes.The fish caught chance of each mesh size is different based on fish species affecting by the gonad maturity level and body circumference.